The Use of English Textbooks at Schools - Maili, Sjafty Nursitti NP; Widyaningrum, Winda (STKIP PGRI Tulungagung, 2025)
English is one of the many languages that must be learned by all levels of school, from elementary to high school. English lessons have been taught in schools for a long time, and the development is so fast that schools are competing to apply it and provide training, webinars, etc. offline and online to improve the ability of English teachers but there are many factors that determine the success of English teachers in the teaching and learning process, one of which is the learning medium, namely English textbooks. In this study, the author uses qualitative research, and the method used is a descriptive method in which the author takes the following steps: First, the author collects five (5) journals related to the analysis of English textbooks; Second, after being collected, the author looks for the results of research and theories that underlie or become a benchmark in analyzing English textbooks by each journal author; Finally, the author gives conclusions based on the journals collected. The result of this research is that in making textbooks, it is necessary to be based on existing theories with not much material content & the material really makes students understand what they are learning.